tg20°*tg40°*tg60°*tg80°=
=tg20°*(tg60-20°)*tg60°*tg(60°+20°)=
= [tg20°*tg(60°-20°)tg(60°+20°)]*tg60°=
=[tg20°*((sin60°-20°)*sin(60°+20°)/(cos(60°-20°)cos(60°+20°))]*√3 =
=[tg20°*(√3/2 *cos20° -1/2 * sin20°)(√3/2 *cos20° +1/2 * sin20°) :
(1/2*cos20°+√3/2 *sin20°)(1/2*cos20°-√3/2 *sin20°)]*√3 =
=[tg20°*(3/4*cos²20°-1/4sin²20°)/(1/4*cos20°-3/4sin20°)]*√3 =
=[(sin20°/cos20°)*(3cos²20°-sin²20°)/(cos²20°-3sin²20°)]*√3=
=[(3cos²20°*sin20°-sin³20°)/(cos³20°-3sin²20°cos20°)]*√3=
=(sin3*20°)/cos(3*20°)*√3= (sin60°)/(cos60°)*√3 = tg60°*√3 =√3*√3=3
4x² - 12x + 9 = 0
D = b² - 4ac = 144 - 16×9 = 0
x = -b/2a
x = 12/8
x = 1,5
2) 5x² + 1 - 6x + 4x² = 0
9x² - 6x + 1 = 0
D = b² - 4ac = 36 - 36×1 = 0
x = -b/2a
x = 6/18
x = 1/3
3) x² + 2x - 3 = 0
D = b² -4ac = 4 - 4×(-3) = 26 = 4²
x1 = ( - 2 + 4) / 2 = 1
x2 = ( - 2 - 4) / 2 = - 3
4) x² + 3x -4 = 0
D = b²- 4ac = 9 - 4×(-4) = 25 = 5²
x1 = ( - 3 + 5) / 2 = 1
x2 = ( - 3 - 5) / 2 = - 4
5) x² - 5x + 4 = 0
D = b² - 4ac = 25 - 4×4 = 9 = 3²
x1 =( 5 + 3) / 2 = 4
x2 = ( 5 - 3) / 2 = 1
6) x² - 4x + 3 = 0
D = b - 4ac = 16 - 4×3 = 4 = 2²
x1 = ( 4 + 2) / 2 = 3
x2 = ( 4 - 2) / 2 = 1
7) 2x² + x - 3x - 4 = 0
2x² - 2x - 4 = 0
x² - x - 2 = 0
D = b² - 4ac = 1 - 4×(-2) = 9 = 3²
x1 = ( 1 + 3) / 2 = 2
x2 = ( 1 - 3) / 2 = - 1
8) 2x² - 3x - 4x + 3 = 0
2x² - 7x + 3 = 0
D = b²- 4ac = 49 - 8×3 = 25 = 5²
x1 = ( 7 + 5) / 4 = 3
x2 = ( 7 - 5)/ 4 = 0,5